Voluntarism and Self-surrender in William James’s Conception of Religion - Viale, Claudio Marcelo (2015)
In this work I hold that William James’s conception of religion is divided between what could be identified as his voluntarism and his idea of self-surrender. In my approach, James’s voluntarism is the heart of The Will to Believe, whereas the idea of self-surrender is the key to understand The Varieties of Religious Experience. These two works respond to a tension in James’s philosophy and canbe seen as two antagonistic intellectual projects. The analysis of this inner tension in James’s conception of religion is the core of this paper. I will also state that his self-surrender notion, unlike his voluntarism, allows us to visualize an essential aspect of James’s conception, that is to say, its morbid aspect.